Penegakan PENEGAKAN HUKUM DAN PERLINDUNGAN KESEHATAN PUBLIK DALAM PERATURAN DAERAH KOTA SURABAYA NO. 2 TAHUN 2019 TENTANG KAWASAN TANPA ROKOK - Dwi Tentri, Septia (Jawa Dwipa, 2025)
Regulation Surabaya City Regulation Number 2 of 2019 is understood as a legal provision that regulates Smoke-Free Areas as a form of effort to protect public health from the dangers of exposure to cigarette smoke. The regulation specifies a number of areas that are prohibited from being used as places for smoking, including health facilities, educational institutions, places of worship, and various other public areas. In addition, the prohibition on the sale and promotion of tobacco products in designated areas is also clearly regulated. The enforcement mechanism in this regulation is regulated through supervision, the imposition of administrative sanctions, and the involvement of relevant authorities to ensure public compliance. The main objective of this regulation is to create a healthy and smoke-free environment, thereby improving the quality of public health in the city of Surabaya in a sustainable manner.